The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18196/jai.190187
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Local Government’s Accountability and Performance: the Isomorphism Institutional Perspective

Abstract: This research aims to explore the accountability and performance of government agency in perspective of institutional theory. It analytically answer two research questions: Do institutional isomorphism exist in the implementation of performance measurement system and accountability in public sector organizations? (RQ1) and Do government agencies actually use performance measurement information to aid decision-making and help plan for future performance improvement? (RQ2). This study is a qualitative research t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
5
16
0
12
Order By: Relevance
“…They found that the developed performance indicators are used mostly to fulfill the regulatory requirements, not to make their organization more effective and efficient. More recently, Ahyaruddin & Akbar (2018) in their study on the implementation of LAKIP in Yogyakarta Province found a similar result. The study unveils the presence of coercive, mimetic and normative pressures in the implementation of the PMS/ SAKIP.…”
Section: Pms In Indonesian Local Governmentsmentioning
confidence: 59%
See 1 more Smart Citation
“…They found that the developed performance indicators are used mostly to fulfill the regulatory requirements, not to make their organization more effective and efficient. More recently, Ahyaruddin & Akbar (2018) in their study on the implementation of LAKIP in Yogyakarta Province found a similar result. The study unveils the presence of coercive, mimetic and normative pressures in the implementation of the PMS/ SAKIP.…”
Section: Pms In Indonesian Local Governmentsmentioning
confidence: 59%
“…The study unveils the presence of coercive, mimetic and normative pressures in the implementation of the PMS/ SAKIP. Consequently, the indicators within the LAKIP is ignored when the government makes a decision and plan the strategies (Ahyaruddin & Akbar, 2018).…”
Section: Pms In Indonesian Local Governmentsmentioning
confidence: 99%
“…Many experts believe that an institutionalization effort of organizational structures and processes tend to appear uniform (isomorphic) with certain rules that are considered good and widely accepted (Ahyaruddin & Akbar, 2018;Akbar et al, 2015;DiMaggio & Powell, 1991DiMaggio & Powell, 1983;Frumkin & Galaskiewicz, 2004;Lai et al, 2006;Sofyani, Akbar, et al, 2018).…”
Section: Literature Review Institutional Theory Within the Village Fumentioning
confidence: 99%
“…Therefore, the accomplishment of an assigned task can be determined by the competence of the people given the task. Noe et al, (2017) Competence can be obtained from formal education and long experiences in carrying out certain tasks (Ahyaruddin & Akbar, 2018;Beckert, 2010;DiMaggio & Powell, 2000;Larson, 1977;Meyer & Rowan, 1977). Based on the previous studies, the competency of the village government human resource plays an important role in achieving village autonomy.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…With regard to the study of public sector organizations, one theory that is widely used, put forward and developed is institutional theory especially in Indonesia, such as; Akbar et al [1], Ahyaruddin and Akbar [9]; [10]. DiMaggio and Powel [11] define institutional theory as a rational response.…”
Section: Literature Review and Hypothesis Formulation Institutionmentioning
confidence: 99%